Flood modelling studies : unsteady flow analysis with HEC-RAS - Teo, He Bei (2014)
HEC-RAS is a River Analysis System developed by the U.S. Army Corps of Engineers that allows the performance of one-dimensional hydraulic calculations for a full network of natural and constructed channels for steady and unsteady flow. An on-going flood modelling studies by the Institute of Catastrophe Risk Management (ICRM) at Nanyang Technological University (NTU) aims to develop a fully integrated flood simulation and damage/loss assessment model through the use of a variety of software, including HEC-RAS. In-depth exploration of the parameters necessary to set up unsteady flow analysis in HEC-RAS can greatly boost the development of this flood simulation mode which currently uses steady state simulation by HEC-RAS. The objective of this project is to define the key parameters relevant to unsteady flow simulation in HEC-RAS and quantify the effects of these parameters. The unsteady flow simulations were benchmarked to the recent 2007 flood event in Jakarta, Indonesia, focusing on the Ciliwung River. Permutations of input parameters were used for unsteady flow simulation and the results were evaluated and compared against that from the steady flow analysis of HEC-RAS. Before execution, it was hypothesised that unsteady flow simulation will yield results comparable to steady flow simulations but with the additional function of time (i.e. duration of flood stage).